UPPER RESPIRATORY TRACT INFECTION WITH BRONCHITIS IN DOMESTIC CATS - Shita Amelia; Putu Devi Jayanti; I Putu Gede Yudhi Arjentinia (Buletin Veteriner Udayana, 2024)
Upper respiratory tract infection (URI) is characterized by irritation and inflammation of the upper respiratory tract, often accompanied by clinical signs such as sneezing, mild coughing, and nasal discharge. This case report discusses the anamnesis, clinical examination, and diagnostic findings to establish a definitive diagnosis and appropriate treatment for a 1.5-year-old female domestic cat named Lucy, weighing 2.5 kg. Lucy presented with sneezing persisting for two months, mucopurulent nasal discharge, loss of voice, and stridor during breathing. Hematological analysis revealed leukocytosis and thrombocytopenia, while cytological examination of the nasal discharge showed neutrophilic infiltration. Thoracic radiographs revealed a bronchial pattern in both lung lobes, and nasal discharge culture tested positive for Pasteurella spp. Based on these findings, Lucy was diagnosed with URI accompanied by bronchitis and treated with a combination of Doxycycline hyclate (10 mg/kg orally, once daily), Methylprednisolone (0.5 mg/kg orally, once daily for 7 days), Bromhexine HCl (1 mg/kg orally, once daily until nasal discharge resolved), and a multivitamin (once daily). On the 8th day of therapy, significant improvement was observed, marked by the resolution of sneezing, absence of nasal discharge, and recovery of the cat's voice. This case underscores the importance of accurate diagnosis and appropriate combination therapy in effectively managing URI and highlights the need for early examination and prompt treatment to prevent complications.